Aplikasi Penambahan Pupuk Organik Padat dan Cair Terhadap Pertumbuhan dan Produksi Tanaman Brokoli (Brassica oleracea L) - Yuliantina Azka; Nova Tri Buyana (Jurnal Agroekoteknologi, 2022)
Broccoli (Brassica oleracea L.) is one of the vegetables that has high selling power and is quite promising for cultivation. This plant can grow in fertile soil conditions, loose and rich in organic matter that is able to meet the nutrient needs of broccoli plants. The fertilization process is very important in determining the quality of cultivated plants. Fertilization using organic fertilizers is believed to be able to produce much higher production than expected by farmers and is environmentally friendly. The application of adding solid and liquid organic fertilizers to broccoli plants is expected to increase growth and production. The research design used was a Factorial Randomized Block Design consisting of two factors. The first factor is doses of solid organic fertilizer which consists of three levels, namely 0%, 25% and 50%. The second factor is doses of liquid fertilizer which consists of four levels, namely 0 ml, 10 ml, 20 ml and 30 ml. The results showed that the addition of solid and liquid organic fertilizers had a significant effect on the parameters of plant height, number of leaves, crop diameter and production of broccoli plants with the highest production in the treatment of 50% solid organic fertilizer with 10 ml of liquid organic fertilizer of 87.4 g.